The Comparative Study of Students’ Ability in Writing Skill between Salaf’s and Khalaf’s Pesantren/ المقارنة بين كفائة الطلبة على الكتابة في المعهد السلفي والخلفي - Dara Mubshirah (Universitas Negeri Malang, 2021)
Arabic is one of the materials studied in Pesantren Khalafi and Salafi. Maharah Kitabah is one of the important skills in learning Arabic. The purpose of this study was to determine the extent of the differences in the kitabah ability of the students in Pesantren Khalafi and Salafi. This study uses a comparative method. Data collection tools used in the form of tests on 50 students of Pesantren Salafi and 50 students Pesantren Khalafi. The data analysis method using by the Mann Whitney statistical test with α= 0,005. The results of this study showed that there was a difference between the maharah kitabah ability of Students in Pesantren Khalafi and Salafi with the statistical value of Arabic writing (p-value (0.016) <α (0.05))تعتبر اللغة العربية إحد المواد الدراسية التي تدرس في المعهد السلفي والخلفي .واللغة العربية هي الإحدى المهارات اللغوية في تعلم اللغة العربية. بالنسبة إلى هذا فإن هذا البحث يهدف إلى التعرف على المقارنة بين كفائة الطلبة على الكتابة في المعهد السلفي والخلفي. إن منهج البحث الذى اعتمدت عليه الباحثة فى كتابة هذه الرسالة هو المنهج المقارن. ولجمع البيانات تقوم بالاختبارات في 50 عينة من الطلبة في المعهد السلفي و50 عينة من الطلبة في المعهد الخلفي. ويتم اختبار الفرضيات باستخدام Mann Whitney من النظام المحسوب بنتيجة = 0،005 . وقد نالت من هنا نتائج البحث المستنتجة من البحوث أن هناك الإختلاف بين كفائة الطلبة في المعهد السلفي والخلفي في كتابة اللغة العربية (p-value (0.016) <α (0.05))